Urinary hydration biomarkers and dietary intake in children - Padrão, Patrícia (2016)
Introduction: The importance of hydration is undoubtable but reliable data on hydration status and its relation with diet is lacking. Objectives: We aimed to evaluate the hydration status and its relation to beverages and food intake in children. Methods: A sample of 172 (50% male), 7-11 year-old children was included in this survey. Participants completed a 24 h urine collection; a 24 hours food recall corresponding to the day of urine collection was applied, weight and height were measured and parents/caregivers fi lled a lifestyle and socio-demographic questionnaire. The free water reserve was used to assess the hydration status. The intakes of food and beverages were compared according to hydration status using the t-test, Mann-Whitney test or unconditional regression models as appropriate. Results: More than half of the participants were classifi ed as hypohydrated or at risk of hypohydration (57% in girls and 58% in boys). Compared to hypohydrated children, a signifi cant higher consumption of water (276.2 ± 208.4 vs 188.2 ± 187.4 g/day) and fruit juices (77.6 ± 139.4 vs 14.4 ± 57.2 g/day) was reported by euhydrated boys and girls, respectively. Lower consumers of water and fruit juices showed a higher risk of hypohydration (OR = 2.16, 95% CI: 1.02-4.58, p= 0.045), adjusting for confounders. Conclusions: Most of the children included in this analysis were classifi ed as at risk of hypohydration and those with higher water and fruit juices consumption showed a better hydration status.